RECONSTRUCTION OF MICRO, SMALL AND MEDIUM ENTERPRISES (MSME) EMPOWERMENT POLICY FROM THE PERSPECTIVE OF PEOPLE'S ECONOMY (EKONOMI KERAKYATAN): AN ANALYSIS OF REGULATIONS AND PUBLIC GOVERNANCE - Simamora, Daniel; Agusta, Ben Indra (Jurnal Administrasi Negara, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are a vital pillar of the Indonesian economy, contributing 61 percent to the Gross Domestic Product in 2024. However, the reality shows that MSME empowerment policies are shifting away from the spirit of the People's Economy (Ekonomi Kerakyatan). Existing policies tend to prioritize market efficiency and procedural ease, largely disregarding the principles of social justice and people's economic sovereignty. This study aims to critically analyze the normative misalignment between the regulatory framework for MSME empowerment, specifically Law Number 20 of 2008, or the Job Creation Law (Undang-Undang Cipta Kerja), and Government Regulation Number 7 of 2021, and the principles of the People's Economy and good public governance. Using a qualitative method through regulatory analysis, this research finds that the policy direction has shifted from substantive empowerment to administrative facilitation. Key findings indicate the dominance of a market efficiency paradigm that trivializes the meaning of empowerment, alongside a lack of space for public participation in policy formulation. As an implication, this study recommends a policy reconstruction that is affirmative towards strengthening collective economic institutions and implementing participatory governance to pursue holistic MSME empowerment.